Influence of time and temperature of ultrasound on anthocyanin content and instrumental color of jambolan pulp (Syzygium jambolanum) (Research, Society and Development, 2020)
The present work aims to evaluate the influence of ultrasound time and temperature on anthocyanin levels and instrumental color measurements of jambolan pulp. The pulp of the jambolão was submitted to an ultrasonic process for 10 and 15 min at 25, 40 and 50 °C at a frequency of 40 kHz, then the fresh pulp and the heat treated pulp were analyzed the following parameters: anthocyanin content and color instrumental (L*, a* and b*). The levels of anthocyanins can be related to the color parameters a* and b*, where the increase in the parameter a* indicates that the color is closer to red, while the decrease in b* indicates that the fruit has color in the blue, the result of these two parameters is directly linked to the amount of pigments in the jambolão shell during the ultrasound process with complementary heating. Ultrasonic treatment with complementary thermal treatment to which the jambolão pulp was subjected, increased the parameters of anthocyanins, luminosity and a*. Being the most expressive difference for higher temperature and longer exposure time to ultrasound.